Participation of young selectors in the recruitment of paediatric specialty trainees. (4th April 2011) - Mann, C; Bryson, L; Budge, H; Wood, D
Abstract : Aims: Young people (YP) have the right to be involved in decisions regarding their healthcare and may be able to offer a unique perspective in the selection and recruitment of medical professionals. We aimed to explore the involvement of young people in selection of candidates to Paediatric Specialty Training. In addition to investigating agreement between consultant and YP scores, we also aimed to evaluate feedback from candidates, YP and consultants on the interview participation process. Methods: We conducted this pilot service evaluation exercise at our regional interviews for entry to run-through training. Local YP were invited to take part and informed consent was obtained from YP and their parents. YP participated in the structured presentation station, with scoring of 31 candidates by panels of two consultants and two YP. For this pilot exercise YP's scores were not included for ranking and appointment. We conducted agreement analysis of scores (Bland Altman) and collated feedback from 5-level Likert scale questionnaires. Results: There was reasonable agreement between consultants and YP with a mean difference of 0.9 (range ±5 points) for presentation scores out of 20. If current consultant scoring were replaced by equally weighted consultant and YP scoring for a single station, 61% (16) of ranked candidates would have seen a change in their ranking. Candidates were deemed unappointable if a minimum score was not achieved; no candidates would have crossed this threshold by the inclusion of YP's scores. Median total score was 117/160 (IQR 23). 83% (43) of feedback respondents believed that YP should be involved in the recruitment of all paediatric trainees. Conclusions: YP were motivated to partake in this participation project and could feasibly be involved in the recruitment and selection process. Consultant colleagues were enthusiastic and positive about YP participation. There was reasonable, but not absolute, agreement between consultant and young interviewers such that ranking but not appointability would be affected in this scenario. We intend to extend training for YP with potential involvement in the communication skills station in future. There is genuine potential to implement YP participation widely throughout medical recruitment and selection processes.